Abakada Pampanga exploring instructional design methods integrated in the mother tongue-based multilingual education teaching methods in the Kapampangan language for children ages 5 to 7 in the kindergarten level of Floridablanca elementary school, Floridablanca, Pampanga - Dela Rosa, Ryan Carlo N.
The Mother Tongue-Based Multilingual Education (MTB-MLE) program of the Department of Education (DepEd) highlights the importance of using the mother tongue as the language of instruction in classrooms as mandated in all public schools across the Philippines. With this program, they aim to produce multilingual learners starting from the kindergarten basic level of education by strengthening their foundation in the mother tongue and as they further progress in the grade school level of the program, Filipino and English languages shall be introduced.